A gene regulatory architecture that controls region‐independent dynamics of oligodendrocyte differentiation. Issue 5 (7th February 2019) - Cantone, Martina; Küspert, Melanie; Reiprich, Simone; Lai, Xin; Eberhardt, Martin; Göttle, Peter; Beyer, Felix; Azim, Kasum; Küry, Patrick; Wegner, Michael; Vera, Julio
Abstract: Oligodendrocytes (OLs) facilitate information processing in the vertebrate central nervous system via axonal ensheathment. The structure and dynamics of the regulatory network that mediates oligodendrogenesis are poorly understood. We employed bioinformatics and meta‐analysis of high‐throughput datasets to reconstruct a regulatory network underpinning OL differentiation. From this network, we identified families of feedforward loops comprising the transcription factors (TFs) Olig2, Sox10, and Tcf7l2 and their targets. Among the targets, we found eight other TFs related to OL differentiation, suggesting a hierarchical architecture in which some TFs (Olig2, Sox10, and Tcf7l2) regulate via feedforward loops the expression of others (Sox2, Sox6, Sox11, Nkx2‐2, Nkx6‐2, Hes5, Myt1, and Myrf). Model simulations with a kinetic model reproduced the mechanisms of OL differentiation only when in the model, Sox10‐mediated repression of Tcf7l2 by miR‐338/miR‐155 was introduced, a prediction confirmed in genetic functional experiments. Additional model simulations suggested that OLs from dorsal regions emerge through BMP/Sox9 signaling. Main points: A comprehensive regulatory network that supports oligodendrocyte high‐throughput data mining. Novel TF‐miRNA circuits elucidated by network analyses. A mathematical model of TF‐miRNA circuits that recapitulates distinct oligodendrogenesis waves.